Pengaruh Motivasi Kerja terhadap Produktivitas Kerja PT. Changshin Indonesia - Sigiro, Sri Devi; Suherman , Enjang; Ratu Khalida , Laras (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of work motivation on employee productivity at PT. Changshin Indonesia. The research method used was quantitative, with data collected through questionnaires distributed to 86 respondents. Data were analyzed using simple linear regression using SPSS version 22 software. The results showed that work motivation had a positive and significant effect on work productivity, with a regression coefficient of 0.781 and a significance level of 0.000 <0.05. The coefficient of determination (R²) of 0.562 indicates that 56.2% of the variation in work productivity is influenced by work motivation, while the remainder is influenced by other factors. In conclusion, the higher the employee's work motivation, the higher the resulting work productivity. Keywords: Work Motivation, Work Productivity, Employees